Diseases of Tropical Fruit Crops 2003
DOI: 10.1079/9780851993904.0241
|View full text |Cite
|
Sign up to set email alerts
|

Diseases of durian.

Abstract: This chapter reviews the distribution, importance and control of disease of durian (Durio zibethinus) together with characteristics and production of the fruit. Important diseases include the green alga Cephaleuros virescens, pink disease (Erythricium salmonicolor [Corticium salmonicolor]) and root rot and patch cankers caused by Phytophthora palmivora. Important causal agents of postharvest fruit rots include Glomerella cingulata, Phytophthora palmivora, Phomopsis durionis, Diplodia theobromae and Fusarium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The leaves turn yellow and drop, followed by a burst of shooting. Patch canker can cause durian trees to become debilitated and finally die if the disease is not well controlled (Lim and Sangchote, 2003).…”
Section: Patch Cankermentioning
confidence: 99%
“…The leaves turn yellow and drop, followed by a burst of shooting. Patch canker can cause durian trees to become debilitated and finally die if the disease is not well controlled (Lim and Sangchote, 2003).…”
Section: Patch Cankermentioning
confidence: 99%
“…The most severe diseases caused by Phytophthora palmivora are patch canker or stem canker, fruit rot, seedling dieback, foliar blight, and root rot [137][138][139]. The pathogen enters plant parts through natural openings or wounds [232].…”
Section: Fungal and Oomycete Diseases Of Durianmentioning
confidence: 99%
“…1). Lim and Sangchote (2003) have been reported that the leaf spot symptom on durian usually presents the small lesions, approximately 1 mm in sizes. However, we initially report distinct observation on lesion size which is larger than 1 mm in diameter with yellow halo in this study.…”
Section: Disease Characteristics and Pathogen Isolationmentioning
confidence: 99%
“…The appropriate climate for the development of durian leaf spot disease was reported to be favored by high humid condition (Lim and Sangchote, 2003). In Thailand, indeed in eastern region, P. durionis spread over durian growing areas throughout the years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation